Successful Hemostasis With Platelet Transfusion and Tranexamic Acid, and Inhibitor Elimination With Cyclosporine, in Steroid-Resistant Acquired Coagulation Factor V Deficiency Caused by Antibiotic Readministration - Kazuto Togitani; Moe Yamamoto; Soichiro Tanaka; Rei Aono; Yoshiki Uemura (Case Reports in Hematology)
Acquired factor V deficiency (AFVD) is a rare coagulation abnormality associated with infectious diseases, antibiotics, surgery, autoimmune diseases, and malignancy, which causality is difficult to prove. Here, we report a case of a 90-year-old woman who developed melena following antibiotic treatment for pneumonia. She had been on cefepime for bacterial pneumonia for 2 months to 2 weeks prior to her arrival in the emergency room. Upon presentation, she had severe anemia (Hb: 6.7 g/dL) and prolonged PT (74.3 s) and activated partial thromboplastin time (APTT) (161.9 s). Coagulation studies revealed incomplete correction of the APTT in a 1:1 mixing study with normal pooled plasma, factor V activity of 0%, and a factor V inhibitor titer of 13 Bethesda units, confirming the diagnosis of AFVD. Since the antibiotics were not recognized as the cause, the coagulation abnormality worsened after their readministration. The melena subsequently improved with platelet transfusion and administration of tranexamic acid, while prednisolone-resistant coagulation abnormalities improved with cyclosporine A (CsA) treatment. This case shows the importance of avoiding suspected drugs and the effectiveness of CsA as a second-line treatment of AFVD.